Seasonal distribution of dissolved inorganic carbon and net community production on the Bering Sea shelf - J. T. Mathis; J. N. Cross; N. R. Bates; S. Bradley Moran; M. W. Lomas; C. W. Mordy; P. J. Stabeno (Biogeosciences, 2010)
In order to assess the current state of net community production (NCP) in the southeastern Bering Sea, we measured the spatio-temporal distribution and controls on dissolved inorganic carbon (DIC) concentrations in spring and summer of 2008 across six shelf domains defined by differing biogeochemical characteristics. DIC concentrations were tightly coupled to salinity in spring and ranged from ~1900 μmoles kg−1 over the inner shelf to ~2400 μmoles kg−1 in the deeper waters of the Bering Sea. In summer, DIC concentrations were lower due to dilution from sea ice melt, terrestrial inputs, and primary production. Concentrations were found to be as low ~1800 μmoles kg−1 over the inner shelf. We found that DIC concentrations were drawn down 30–150 μmoles kg−1 in the upper 30 m of the water column due to primary production and calcium carbonate formation between the spring and summer occupations. Using the seasonal drawdown of DIC, estimated rates of NCP on the inner, middle, and outer shelf averaged 28 ± 9 mmoles C m−2 d−1. However, higher rates of NCP (40–47 mmoles C m−2 d−1) were observed in the "Green Belt" where the greatest confluence of nutrient-rich basin water and iron-rich shelf water occurs. We estimated that in 2008, total NCP across the shelf was on the order of ~96 Tg C yr−1. Due to the paucity of consistent, comparable productivity data, it is impossible at this time to quantify whether the system is becoming more or less productive. However, as changing climate continues to modify the character of the Bering Sea, we have shown that NCP can be an important indicator of how the ecosystem is functioning.